INPUT AND OUTPUT RATES OF SOME CHEMICAL SOLUTES IN SOROCABA RIVER - da Silva, Alexandre Marco; Rosa, André Henrique; Muniz Silveira, Felipe; da Silva Vaz, Samuel; Silva de Oliveira, Guilherme (Revista de Estudos Ambientais, 2008)
Considering the physical and chemical characteristics of the water of an aquatic ecosystem represent the result of the integration of many environmental factors, the aim of this study is presenting information about the rates of import and export of three inorganic nutrients in the Sorocaba River (part of the river that flows exactly within the Sorocaba city) and analyzing the effects of the land use and of the existence of effluents along the study area. After the sampling, the concentration of phosphate, nitrate and sulfate were determined in laboratory, by using the colorimetric method, for each one of the twenty four collected samples. Additionally, hydrological database was obtained from internet in order to estimate the import / export rates of the investigated compounds. The surveyed results indicate, respectively, rates of input and output of nitrite: 0.81 t x year-1 and 64.24 t x y-1; of phosphate 243.95 t x y-1 and 130.10 t x y-1 and sulfate 2,439.5 t x y-1 and 6,098.8 t x y-1. The study area also was considered eutrophic in the major part of the river, and hyper-eutrophic on four sampling points. So, it can be concluded that the studied water course, due to pass by a highly urbanized area and just after in a rural area, acts a source of nitrite and sulfate and as a sink of phosphate and it is strongly disturbed biogeochemically. Keywords: Nutrients input and output. Environmental impact. Water resources. Sorocaba River. Water pollution.